Labor Supply and Productivity Responses to Non-Salary Benefits: Do They Work? If So, at What Level Do They Work Best? - Marilyn Spencer; Deniz Gevrek; Valrie Chambers; Randall Bowden (Institute for the Study of Labor (IZA), 2015)
This study explores the impact of a particular low marginal-cost employee benefit on employees' intended retention and performance. By utilizing a unique data set constructed by surveying full-time faculty and staff members at a public university in the United States, we study the impact of this employee benefit on faculty and staff performance and retention. We focus on the impact of reduction in dependent college tuition at various levels on employees' intentions to work harder and stay at their current job by using both OLS and Ordered Probit models. We also simulate the direct opportunity cost (reduction in revenue) in dollars and as a percent of total budgeted revenue to facilitate administrative decision making. The results provide evidence that for institutions where employee retention and productivity are a priority, maximizing or offering dependent college tuition waiver may be a relatively low-cost benefit to increase intended retention and productivity. In addition, the amount of the tuition waiver, number of dependents and annual salary are statistically significant predictors of intended increased productivity and intent to stay employed at the current institution. Employee retention and productivity is a challenge for all organizations. Although pay, benefits, and organizational culture tend to be key indicators of job satisfaction, little attention is given to specific types of benefits. This study is the first comprehensive attempt to explore the relationship between the impact of this low-cost employee benefit and employee performance and retention in a higher education institution in the United States.
Keywords: J22; J32; J45; M52; 330; higher education; retention; employee satisfaction; productivity; job satisfaction; fringe benefits